PEMBINAAN INTEGRATED MANAGEMENT SYSTEM PADA YAYASAN BAIT TA’ALAMAL QUR’AN BATAM - Daris Purba; Suratman; Pastima Simanjuntak; Nasruji; Zara Tania Rahmadi (ASOSIASI IDEBAHASA KEPRI, 2022)
Many educational institutions do not yet have an integrated management system. Like industry and Health, Educational institutions are also an activity that needs to have a good management system because it has a cycle of activities that are more or less the same as the industrial world. This community service seeks to apply the results of research on the Integrated Management System (IMS) to educational institutions at the Bait Tahfiz Ta'alamal Qur'an Foundation. The method of implementing the service is carried out by discussion and workshop methods. This service activity concludes that the application of IMS in educational institutions has a significant impact on improving management in every aspect.